Livelihood Strategies for Coping with Land Loss among Households in Vietnam's Sub-Urban Areas - Tran, Quang Tuyen (2016)
Using a novel data set from my household survey in a sub-urban district of Hanoi, Vietnam, this study is the first attempt using an econometric approach to investigate the relationship between farmland loss and households' livelihood strategies. The results from the multinomial logit model provide the first econometric evidence that land loss increases with the probability of households adopting a strategy specializing in a single nonfarm activity or diversifying in many activities.